RF transmitter using 33% duty cycle LO signal for harmonic suppression - Wang, Peng (2017)
Due to the increasing demand for communication bandwidth combined with scarceness of free spectrum, spectral efficiency has been a challenge to the development of 4th generation RF communication system. In particular, the Long-Term-Evolution (LTE) standard groups the OFDM subcarriers into Resource Blocks to dynamically allocate within the channel bandwidth. However, during this process, due to the limited linearity of transmit path, harmonic distortion components named counter intermodulation products (CIM) are generated. The CIM products may fall directly or through cross-modulation into the receiver (RX) band, thus degrading the frequency division duplexing performance. CIM products may also fall into the protected bands and violate spectral emission requirement. Recently, CIM products, especially for counter 3rd-order intermodulation products (CIM3) due to 3rd-order nonlinearity in the transmit path, has been recognized as an important design parameter for LTE RF system. Two main contributors of the CIM3 have been identified in the previous literatures. The first and minor contributor comes from the baseband 3rd-order nonlinearity; the second and major contributor is due to the intermodulation between the wanted signal and the local oscillator (LO) signal’s 3rd-order harmonic component. Targeting for the solution of the second contributor, an RF transmitter (TX) employing passive mixer based architecture is demonstrated in previous literature. The 33% duty cycle LO scheme is used since it intrinsically does not have 3rd-order harmonic. Thus the intermodulation with 3×LO (3LO) frequency component is avoided. As a result, CIM3 is suppressed at the RF output. This technique is not sensitive to device matching and calibration is not a pre-requisite. Since 3LO filtering requirement can be alleviated, the bill-of-material cost is reduced. This thesis is the continuous work of the previous literature to explore the 33% duty cycle LO scheme. An RF transmitter employing 33% duty cycle LO is proposed in this thesis. The implementation of the system in this thesis is based on active mixer approach which is different from previous literature. A wide band test frequency range is also provided in this thesis. Besides, each block design are explained in details in the thesis. This TX prototype was fabricated in GlobalFoundries (GF) RF CMOS 180 nm process. The TX active core occupies 1.4 mm × 0.5 mm including RF front-end as well as analog baseband. The design was tested on PCB with Rogers 4350. The measurement result shows that the designed TX achieves a power gain of 11 dB when VGA is set to the lowest bit. The operation frequency is from 350 MHz to 1.35 GHz. The output 1 dB compression point is measured at -0.7 dBm and the output 3rd-order intercept point is 8.3 dBm at the frequency of 782 MHz. The measured CIM3 and 3LO frequency component are less than -60 dBc and -45 dBc respectively up to output 1 dB compression point. The designed circuit also shows the consistency for the suppression of CIM3 to be less than -60 dBc over whole operating frequency. The power consumption of this TX is 190.8 mW with 1.8 V supply voltage.